ANALISIS PENGARUH SELF ASSESSMENT SYSTEM, SOSIALISASI PERPAJAKAN, ACCOUNT REPRESENTATIVE, SANKSI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN (Studi Empiris Pada Wajib Pajak UMKM di KPP Semarang Timur) - Christian Hadi Soemarsono, 13.05.52.0086; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of self assessment system, tax sosialitation, account representative, tax penalties and awareness taxprayer which directly influence acceptance of knowledge and understanding of taxation. The population in this study were all UMKM taxpayer in KPP Semarang Timur. Sampling was done using conveniance sampling method and sample size were 100 respondents. The primary data collection method used survei method was used a questionnaire . Data were analyzed using multiple linier regression model. Result of research indicate that the variables: self assessment system, tax sosialitation, account representative, and tax penalties have significant positif effect to acceptance of knowledge and understanding of taxation, awareness taxprayer do not has a effect to acceptance of knowledge and understanding of taxation.Keywords: UMKM, Self Assessment System, Tax Sosialitation, Account Representative, Tax Penalties, Awareness Taxprayer, Knowledge and Understanding of Taxation